Mosque-Based Economic Empowerment as Living Sharia Economic Law: Principles and Challenges - Yenti Sumarni; Desi Isnaini; Eka Sri Wahyuni (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2025)
This study analyzes mosque-based economic empowerment as a form of community implementation of Sharia economic law beyond formal Islamic financial institutions. Using a qualitative, exploratory approach through interviews and focus group discussions, this research investigates how mosques serve as sites for sharia-compliant economic practices, including cooperatives, microfinance, and community entrepreneurship. The findings indicate that mosque-based economic activities reflect core principles of Islamic economic law, including justice, mutual consent, the prohibition of usury, and public benefit. However, normative challenges persist due to the lack of inclusive policies and structured governance, as well as limited formal institutional support. Overall, this study highlights mosque-based economic empowerment as a dynamic expression of living Islamic economic law. Keywords: mosque-based economic empowerment; sharia economic law; Islamic entrepreneurship Abstrak Penelitian ini menganalisis pemberdayaan ekonomi berbasis masjid sebagai bentuk implementasi hukum ekonomi Syariah oleh masyarakat, di luar lembaga keuangan Islam formal. Dengan pendekatan kualitatif dan eksploratif melalui wawancara dan diskusi kelompok terfokus, penelitian ini menggali bagaimana masjid berperan sebagai tempat mempraktikan aktivitas ekonomi yang sesuai syariah, termasuk koperasi, pembiayaan mikro, dan kewirausahaan. Hasil penelitian ini menunjukkan bahwa kegiatan ekonomi berbasis masjid mencerminkan prinsip-prinsip pokok hukum ekonomi Islam, seperti keadilan, kesepakatan bersama, larangan riba, dan manfaat bagi masyarakat. Namun, tantangan normatif tetap ada karena kurangnya kebijakan inklusif, tata kelola yang terstruktur, serta dukungan lembaga formal. Secara umum, penelitian ini menegaskan bahwa kewirausahaan berbasis masjid merupakan ekspresi dinamis dari hukum ekonomi Islam yang hidup di masyarakat. Kata Kunci: pemberdayaan ekonomi berbasis masjid; hukum ekonomi syariah; kewirausahaan Islam